Changes in inflammatory cytokines, antioxidants and liver stiffness after chelation therapy in individuals with chronic lead poisoning - Tongluk Teerasarntipan; Roongruedee Chaiteerakij; Piyapan Prueksapanich; Duangporn Werawatganon (BMC Gastroenterology, 2020)
Abstract Background Chronic exposure to lead causes lead to accumulate mainly in the liver. In vivo studies have shown that lead toxicity is related to alterations in the inflammatory response. We aimed to evaluate the association between lead poisoning and liver fibrosis as well as the change in the degree of liver fibrosis, levels of inflammatory mediators and glutathione (GSH) after chelation therapy. Methods Workers from a battery factory who were exposed to lead for > 12 months and had a blood lead level (BLL) > 70 μg/dL were enrolled (n = 86) in the study. Participants underwent chelation therapy with intravenous CaNa2EDTA for 2 days followed by treatment with oral D-penicillamine for 90 days. The primary outcome was the change in the degree of liver fibrosis, which was presented as liver stiffness (LS) measured by FibroScan®. Secondary outcomes were the changes in the levels of serum GSH and inflammatory mediators such as tumor necrosis factor-alpha (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6) after chelation therapy. Results Among the 86 participants, there was a positive correlation between the duration of lead exposure and LS (r = 0.249, p = 0.021). To avoid the confounding effect of obesity-related steatosis, only 70 individuals who had controlled attenuation parameters < 296 dB/m, BMI < 25 kg/m2 and normal waist circumference were included in the interventional analysis. After chelation, the mean LS significantly decreased from 5.4 ± 0.9 to 4.8 ± 1.4 kPa (p = 0.001). Similarly, all of the inflammatory cytokines studied significantly decreased after chelation (p < 0.001); TNF-α decreased from 371.6 ± 211.3 to 215.8 ± 142.7; the levels of IL-1β decreased from 29.8 ± 1.7 to 25.9 ± 4.3; and the levels of IL-6 decreased from 46.8 ± 10.2 to 35.0 ± 11.9. On the other hand, the mean GSH level increased significantly from 3.3 ± 3.3 to 13.1 ± 3.7 (p < 0.001) after chelation therapy. Conclusion The duration of lead exposure was significantly correlated with the degree of liver fibrosis. Chelation treatment was associated with increased levels of GSH and decreased levels of proinflammatory cytokines and could potentially reduce the degree of LS. Trial registration This study was retrospectively registered and approved by the Thai Clinical Trial Registry (TCTR) on 2019-11-07. The TCTR identification number is TCTR20191108001 .